A new inorganic photolabile protecting group for highly efficient visible light GABA uncaging - Zayat, Leonardo Martin (2007)
Inhibiting with visible light. An inorganic‐based caged compound of the inhibitory neurotransmitter, γ‐amino butyric acid (GABA), was prepared and photolysed by light at 450 nm with the highest uncaging quantum yield reported to date. GABA ion channels were activated by irradiation in a biological preparation by using this caged compound. (Image courtesy of the CNS Forum http://www.cnsforum.com)